The presence of harmful algae in the coastal waters of Bintan Island, Riau Islands - Tri Apriadi; Winny Retna Melani; Andi Zulfikar; Deni Sabriyati; Wahyu Muzammil; Nuralim Pasisingi (Depik, 2024)
Environmental mitigation measures are being undertaken as a proactive approach to prevent the adverse consequences associated with Harmful Algal Blooms (HABs). Presently, there is a lack of comprehensive information regarding the occurrence of HABs in the waters surrounding Bintan Island, and routine monitoring to assess the potential for eutrophication is absent. This research should begin by gathering information about potential sources that contribute to the emergence of HABs, the specific types of algae with the capacity to trigger HABs The primary objective of this study is to identify the harmful algae species present in the coastal waters of Bintan Island. The research was conducted in August 2023, with the sampling process taking place at four specific locations within the coastal waters of Bintan Island. These sampling stations were selected deliberately to capture the varying activities predominant in each respective area. The microalgae found consisted of four groups, namely Bacillariophyta, Cyanophyta, Dinophyta, and Chlorophyta. Bacillariophyta is a group of microalgae with the highest abundance proportion at all observation stations. Harmfull Algae found in the coastal waters of Bintan Island generally come from the Dinophyta group of the types Ceratium sp., Peridinium sp., Prorocentrum sp., and Dinophysis sp. Harmful microalgae from the Dinophyta group were found at all research stations, with the highest proportion of abundance at Station 2 (6%) and the lowest at Station 3 (1%). The difference in these findings is thought to be due to the dynamics of the hydrosanographic parameters of the waters, especially nutrient concentrations.Keywords:BintanCeratiumDinophytaHarmfulMicroalgae